VERTICAL CONTROL OF OVERBITE IN MIXED DENTITION BY TRAINER SYSTEM - Miroslava Dinkova (Journal of IMAB, 2014)
Purpose. The purpose of this study is to follow-up the biometrical and skeletal vertical changes in patients with deep overbite in mixed dentition after a functional orthodontic treatment with Trainer System™ is conducted. Material and Methods. 32 patients (20 girls and 12 boys) with deep overbite in mixed dentition were followed-up. An orthodontic treatment with Trainer System™, including Trainer for kids (T4K)-blue, T4K-red and Myobrace was conducted. The recommended time for wearing the appliances was 8–12 hours, mostly at the night and 1–2 hours total time during the day. All the patients were photo-documented. Impressions, panoramic radiographs and lateral cephalograms were taken before the beginning of the treatment and at the end of every single step in relation with every change of appliances. Comparative biometrical and cephalometric analyses were made. The data was statistically processed. Results. The comparative biometrical analyses showed reduction of overbite with 2.5–3.5 mm after the end of the orthodontic treatment. 62% of cases showed relapse from 0.5 to 1mm. After the end of the orthodontic treatment an inclination of upper and lower incisors and changes with M/SN, М/F, ANB, SNA, SNB values were established. Conclusions. If untreated during the growing period, deep overbite leads to serious functional disorders, pathologic abrasion and myo-articular problems. Myofunctional Trainer System™ is successfully applied in the management of deep overbite in growing kids with early mixed dentition. The design of appliances helps the right positioning of tongue and jaws, removes bad habits, harmonizes tooth arches, corrects the vertical problems.